Rapid and on-site wireless immunoassay of respiratory virus aerosols via hydrogel-modulated resonators - Li, Xin; Sun, Rujing; Pan, Jingying; Shi, Zhenghan; An, Zijian; Dai, Chaobo; Lv, Jingjiang; Liu, Guang; Liang, Hao; Liu, Jun; Lu, Yanli; Zhang, Fenni; et al. (Nature communications, 2024)
Rapid and accurate detection of respiratory virus aerosols is highlighted for virus surveillance and infection control. Here, we report a wireless immunoassay technology for fast (within 10 min), on-site (wireless and battery-free), and sensitive (limit of detection down to fg/L) detection of virus antigens in aerosols. The wireless immunoassay leverages the immuno-responsive hydrogel-modulated radio frequency resonant sensor to capture and amplify the recognition of virus antigen, and flexible readout network to transduce the immuno bindings into electrical signals. The wireless immunoassay achieves simultaneous detection of respiratory viruses such as severe acute respiratory syndrome coronavirus 2, influenza A H1N1 virus, and respiratory syncytial virus for community infection surveillance. Direct detection of unpretreated clinical samples further demonstrates high accuracy for diagnosis of respiratory virus infection. This work provides a sensitive and accurate immunoassay technology for on-site virus detection and disease diagnosis compatible with wearable integration. Infectious respiratory viruses have been an everlasting threaten to public health. Here, authors report a wireless immunoassay technology based on immuno-responsive hydrogel-modulated resonant sensors, which facilitate on-site respiratory virus surveillance.